Automorphism invariant modules on the right Goldie ring - Lê, Văn Thuyết; Trang, Đào Thị; Trương, Công Quỳnh (Hue University Journal of Science: Natural Science, 2022)
In this paper, we study some properties of automorphism invariant modules on the right Goldie ring and state some properties related to this class of modules. In addition, we confirmed some problems related to the nonsingular automorphism invariant ring.